Concept analysis of the independent learning curriculum in the mass of Covid-19 at early childhood education institutions - Rahayu, Cucu; Warlizasusi, Jumira; Ifnaldi, Ifnaldi; Khairiah, Dina (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2022)
Independent learning (Merdeka Belajar) is the latest discovery in the field of Early Childhood Education. Institutions, teachers, and students have the flexibility to organize their learning activities when they have the freedom to learn. For PAUD teachers, the problem of learning independence is a matter of the ability to communicate and adapt to changes in the world of education. This study aimed to analyze the concept of an independent learning curriculum. This study uses qualitative methods, data sources from journals, research reports, scientific articles, etc. The data collection technique in this study uses source triangulation and technical triangulation. The data analysis technique in this study used SWOT analysis. The author's study results in the concept of Independent learning in PAUD is Freedom to Play. The idea is child-centered, and so far, learning is mostly teacher-centered. The characteristics of the curriculum are children. Teachers can develop their learning themes that will be implemented and efforts to increase creativity in learning based on their relationship with independent learning. Therefore, the learning process can provide free space for educators and students to be more creative in learning. This study found that independent learning gives schools the flexibility to determine learning materials that aim to develop better students.